Automated feedback test generation and functionality testing for UI development with self-guided recommendation - Hasan, Md.Tanvir; Durjoy, S.M. Hazzaz; Hasan, Jahidul; Binte Zafar, Mahazabin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.